Stable overexpression and targeted gene deletion of the causative agent of ash dieback Hymenoscyphus fraxineus - Tobias Lutz; Birgit Hadeler; Mareike Jaeckel; Barbara Schulz; Cornelia Heinze (Fungal Biology and Biotechnology, 2023)
Abstract Background Due to the infection with the invasive ascomycete Hymenoscyphus fraxineus, which has been replacing the closely related and non-pathogenic native Hymenoscyphus albidus, the European ashes, Fraxinus excelsior (also known as the common ash), Fraxinus angustifolia (also known as narrow-leaved ash) and Fraxinus ornus (also known as the manna ash) are at risk. Hymenoscyphus fraxineus is the causative agent of ash dieback of the European ashes, but is non-pathogenic to the native Asian ash Fraxinus mandshurica (also known as the Manchurian ash). Even though the invasion of H. fraxineus is a great threat for ashes in Europe, the fungal biology is still poorly understood. By the use of live cell imaging and targeted gene knock-out, the fungal life cycle and host–pathogen interaction can be studied in more detail. Results Here, we developed a protocol for the preparation of protoplasts from mycelium of H. fraxineus, for their regeneration and for stable transformation with reporter genes and targeted gene knock-out by homologous recombination. We obtained mutants with various levels of reporter gene expression which did not correlate with the number of integrations. In an in vitro infection assay, we demonstrated the suitability of reporter gene overexpression for fungal detection in plant tissue after inoculation. As a proof of principle for targeted gene knock-out, the hygromycin resistance cassette of a reporter gene-expressing mutant was replaced with a geneticin resistance cassette. Conclusions The invasive fungal pathogen H. fraxineus is threatening the European ashes. To develop strategies for pest management, a better understanding of the fungal life cycle and its host interaction is crucial. Here, we provide a protocol for stable transformation of H. fraxineus to obtain fluorescence reporter strains and targeted gene knock-out mutants. This protocol will help future investigations on the biology of this pathogen.